The Use of The Quick Response Code Indonesian Standard (QRIS) in Indonesia-Thailand Economic Interaction - Amalia Nur Azizah; Etha Pasan (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
Indonesia already has a Local Currency Transaction (LCT), a cross-border payment system that uses local currency to support international trade between partner countries. However, in 2021, Bank Indonesia issued a cross-border payment system called QRIS cross-border and invited neighboring countries, namely Thailand, to cooperate by using the QR code-based payment tool. Seeing this, LCT actually has adventages such as being able to reduce dependence on the US Dollar, the liquidity of the Rupiah and Bath currencies is more guaranteed and hedging costs will be more affortdable, which are also included in the QRIS system. This raises questions about what interest Indonesia has in offering to re-offer cooperation with Thailand through QRIS, even though LCT has provided similar benefits. This study aims to explain Indonesia’s interests in using QRIS cross-border within the framework of LCS cooperation towards economic interaction with Thailand.